Dielectric material and multilayer ceramic electronic component comprising the same
Patent Information
- Application Number
- CN202111669037.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-12-31
- Filing Date
- 2021-12-31
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2041-12-31
AI Technical Summary
With the miniaturization and ultra-high capacitance of multilayer ceramic electronic components, the dielectric layer becomes thinner, leading to a deterioration in withstand voltage characteristics, reliability, and high-temperature withstand voltage characteristics. It is also difficult to maintain a high effective dielectric constant or capacitance under DC bias voltage, while preventing the degradation of reliability, etc.
The dielectric material is composed mainly of (Ba1-xCax)(Ti1-y(Zr,Sn,Hf)y)O3, combined with rare earth elements such as Y, Dy, Ho, Er, Gd, Ce, Nd, Sm, Nb, Tb, Eu, Tm, La, Lu and Yb as the first secondary component, Si and/or Al as the second secondary component, and Ba and/or Ca as the third secondary component, satisfying a specific molar ratio relationship to control the distribution of grains and grain boundaries, thereby enhancing the Schottky barrier, reducing oxygen vacancies, and suppressing charge conduction.
This method achieves the maintenance of high dielectric constant and excellent withstand voltage characteristics in thin dielectric layers, improving the reliability and high-temperature stability of multilayer ceramic electronic components and suppressing the generation and conduction of charges inside the grains.
Smart Images

Figure CN114694959B_ABST
Abstract
Description
[0001] This application claims the benefit of priority to Korean Patent Application No. 10-2020-0189832, filed on December 31, 2020, with the Korean Intellectual Property Office, the entire disclosure of which is incorporated herein by reference. Technical Field
[0002] This disclosure relates to a dielectric material and a multilayer ceramic electronic component including the dielectric material. Background Technology
[0003] Recently, with the trend of miniaturization in electronic products, multilayer ceramic electronic components also need to be miniaturized and have high capacitance. The dielectric layer of multilayer ceramic electronic components has also become thinner to meet the requirements of miniaturization and large capacitance.
[0004] Furthermore, it is well known that the withstand voltage characteristics of electronic components are significantly affected by the internal microstructure of the component. As the dielectric layer becomes thinner, the grain size and composition distribution of the dielectric layer are affected, which may lead to a deterioration in the withstand voltage and reliability characteristics of multilayer ceramic electronic components. Typically, grain boundaries between grains in electronic components have high resistivity components; therefore, research has been conducted to provide electronic components with high reliability by increasing the ratio of grain boundaries within the dielectric layer.
[0005] However, with the miniaturization and ultra-high capacitance of electronic components, the dielectric layer becomes thinner, thus issues such as degradation of product reliability, high-temperature withstand voltage characteristics, and DC bias characteristics still exist. Furthermore, there is an increasing demand for characteristics that achieve a high effective dielectric constant or capacitance under applied DC bias voltage while preventing the aforementioned reliability degradation. Summary of the Invention
[0006] One aspect of this disclosure provides dielectric materials and multilayer ceramic electronic components with high dielectric constant and excellent withstand voltage characteristics.
[0007] One aspect of this disclosure also provides dielectric materials and multilayer ceramic electronic components with excellent high-temperature reliability.
[0008] One aspect of this disclosure also provides dielectric materials and multilayer ceramic electronic components that can control the second same while providing excellent dielectric density and microstructure uniformity.
[0009] According to one aspect of this disclosure, a dielectric material may include: a main component (or main part), composed of (Ba 1-x Ca x (Ti) 1-y (Zr,Sn,Hf) yO3 (0≤x≤1 and 0≤y≤0.5) represents the following: a first subcomponent (or first auxiliary component) comprising at least one element selected from Y, Dy, Ho, Er, Gd, Ce, Nd, Sm, Nb, Tb, Eu, Tm, La, Lu, and Yb; a second subcomponent comprising Si and / or Al; and a third subcomponent comprising Ba and / or Ca, and satisfying at least two of the following relations 1 to 6: 0.162≤M Tb / M Dy ≤1.20 [Relationship 1] 0.176≤M Gd / M Dy ≤0.60 [Relationship 2] 0.081≤M Sm / M Dy ≤0.176 [Relationship 3] 0.081≤M Nb / M Dy ≤0.176 [Relationship 4] 0.60≤M2 / M1≤1.36 [Equation 5] 0.263≤M3 / M2≤0.455 [Equation 6] Among them, in relation 1 to relation 4, M Tb M Dy M Gd M Sm and M Nb These are, respectively, the sum of the B-site elements relative to 100 moles of the principal component, the number of moles of Tb, Dy, Gd, Sm, and Nb in the first subcomponent, and in Relations 5 and 6, M1 is the sum of the B-site elements relative to 100 moles of the principal component, the total number of moles of the first subcomponent, M2 is the sum of the B-site elements relative to 100 moles of the principal component, the total number of moles of the second subcomponent, and M3 is the sum of the B-site elements relative to 100 moles of the principal component, the total number of moles of the third subcomponent.
[0010] According to one aspect of this disclosure, a dielectric material may include: a main component, composed of (Ba... 1-x Ca x (Ti) 1-y (Zr,Sn,Hf) yThe designation is O3 (0≤x≤1 and 0≤y≤0.5); and a plurality of grains, the surfaces of which are coated with a second sub-component comprising Si and / or Al, and grain boundaries are provided between two or more grains. The average diameter D1 of the core of the grain is greater than or equal to 5 nm and less than or equal to 100 nm, and the average diameter D2 of the grain is greater than or equal to 50 nm and less than or equal to 600 nm.
[0011] According to another aspect of this disclosure, a multilayer ceramic electronic component may include: a ceramic body including a dielectric layer and a first inner electrode and a second inner electrode; and a first outer electrode and a second outer electrode disposed on the outer surface of the ceramic body and respectively connected to the first inner electrode and the second inner electrode, wherein the dielectric layer includes: a main component composed of (Ba 1-x Ca x (Ti) 1-y (Zr,Sn,Hf) y O3 (0≤x≤1 and 0≤y≤0.5) represents; the first subcomponent includes at least one element selected from Y, Dy, Ho, Er, Gd, Ce, Nd, Sm, Nb, Tb, Eu, Tm, La, Lu and Yb; the second subcomponent includes Si and / or Al; and the third subcomponent includes Ba and / or Ca, and can satisfy at least two of the following relations 1 to 6.
[0012] 0.162≤M Tb / M Dy ≤1.20 [Relation 1].
[0013] 0.176≤M Gd / M Dy ≤0.60 [Relation 2].
[0014] 0.081≤M Sm / M Dy ≤0.176 [Relation 3].
[0015] 0.081≤M Nb / M Dy ≤0.176 [Relation 4].
[0016] 0.60≤M2 / M1≤1.36 [Relationship 5].
[0017] 0.263≤M3 / M2≤0.455 [Relationship 6].
[0018] In relations 1 to 4, M Tb M Dy M Gd M Sm and M NbThese are, respectively, the sum of the B-site elements relative to 100 moles of the principal component, the number of moles of Tb, Dy, Gd, Sm, and Nb in the first subcomponent, and in Relations 5 and 6, M1 is the sum of the B-site elements relative to 100 moles of the principal component, the total number of moles of the first subcomponent, M2 is the sum of the B-site elements relative to 100 moles of the principal component, the total number of moles of the second subcomponent, and M3 is the sum of the B-site elements relative to 100 moles of the principal component, the total number of moles of the third subcomponent.
[0019] According to another aspect of this disclosure, a multilayer ceramic electronic component may include: a ceramic body including a dielectric layer and a first inner electrode and a second inner electrode; and a first outer electrode and a second outer electrode disposed on the outer surface of the ceramic body and respectively connected to the first inner electrode and the second inner electrode. The dielectric layer may include: a main component composed of (Ba... 1-x Ca x (Ti) 1-y (Zr,Sn,Hf) y The matrix is represented by O3 (0≤x≤1 and 0≤y≤0.5), and includes a plurality of grains, the surfaces of which are coated with a second sub-component comprising Si and / or Al, and grain boundaries are provided between two or more grains. The average diameter D1 of the core of the grains may be greater than or equal to 5 nm and less than or equal to 100 nm, and the average diameter D2 of the grains may be greater than or equal to 50 nm and less than or equal to 600 nm. Attached Figure Description
[0020] The above and other aspects, features and advantages of this disclosure will be more clearly understood from the following detailed embodiments, taken in conjunction with the accompanying drawings, in which: Figure 1 This is a schematic perspective view of a multilayer ceramic electronic assembly according to exemplary embodiments of the present disclosure; Figure 2 It is shown schematically. Figure 1 A three-dimensional view of the ceramic body; Figure 3 It is along Figure 1 A cross-sectional view taken from line I-I'; Figure 4 yes Figure 3 A magnified view of region A; Figure 5 It is shown schematically. Figure 4 A diagram of the grains; and Figure 6 It is a SEM image of the principal component according to an exemplary embodiment of the present disclosure. Detailed Implementation
[0021] Exemplary embodiments of this disclosure will now be described in detail with reference to the accompanying drawings.
[0022] In the accompanying drawings, the X direction can be defined as a first direction, the L direction, or the length direction; the Y direction can be defined as a second direction, the W direction, or the width direction; and the Z direction can be defined as a third direction, the T direction, or the thickness direction.
[0023] This disclosure relates to dielectric materials, and the dielectric materials according to this disclosure are used in electronic components. Electronic components incorporating the dielectric materials of this disclosure may include, but are not limited to, capacitors, inductors, piezoelectric elements, varistors, or thermistors.
[0024] The dielectric material according to exemplary embodiments of this disclosure may include: a main component, composed of (Ba 1-x Ca x (Ti) 1-y (Zr,Sn,Hf) y O3 (0≤x≤1 and 0≤y≤0.5) represents; the first subcomponent includes at least one element selected from Y, Dy, Ho, Er, Gd, Ce, Nd, Sm, Nb, Tb, Eu, Tm, La, Lu and Yb; the second subcomponent includes Si and / or Al; and the third subcomponent includes Ba and / or Ca, and can satisfy at least two of the following relations 1 to 6.
[0025] 0.162≤M Tb / M Dy ≤1.20 [Relationship 1] 0.176≤M Gd / M Dy ≤0.60 [Relationship 2] 0.081≤M Sm / M Dy ≤0.176 [Relationship 3] 0.081≤M Nb / M Dy ≤0.176 [Relationship 4] 0.60≤M2 / M1≤1.36 [Equation 5] 0.263≤M3 / M2≤0.455 [Relationship 6] In relations 1 to 4, M Tb M Dy M Gd M Sm and M NbM1 represents the total number of moles of each component (Tb, Dy, Gd, Sm, and Nb) in the first subcomponent relative to 100 moles of the principal component (B-site elements). In Relations 5 and 6, M1 represents the total number of moles of the first subcomponent relative to 100 moles of the principal component (B-site elements), M2 represents the total number of moles of the second subcomponent relative to 100 moles of the principal component (B-site elements), and M3 represents the total number of moles of the third subcomponent relative to 100 moles of the principal component (B-site elements). In one example, equation M... Xy It can represent the total number of B-site elements relative to 100 moles of the principal component, or the number of moles of element Xy.
[0026] Typically, by increasing the grain boundary fraction in dielectric materials, which include both grains and grain boundaries, the charge mobility can be reduced by utilizing the potential barrier at the interface. To this end, dielectric materials with small grain distributions have been studied to increase the grain boundary fraction. However, as the thickness of the dielectric material decreases, the electric field strength increases rapidly, and the Schottky barrier often relatively decreases. Therefore, it is difficult to ensure the reliability of dielectric materials in ultrathin environments solely by controlling the grain distribution.
[0027] Furthermore, during the manufacturing process of electronic components, firing is carried out in a reducing atmosphere to prevent oxidation of electrodes, etc. However, due to the low oxygen partial pressure, oxygen vacancies and electrons are formed. Therefore, in order to improve the reliability of the grain interior in the ultrathin layer environment, it is necessary to control the ionic conductivity caused by oxygen vacancies and the electronic conductivity of electrons / holes.
[0028] The inventors have discovered that, through Equations 1 to 6 above, the Schottky barrier can be enhanced by uniformly distributing components with higher work functions than the principal components within the grain boundaries, while simultaneously reducing the amount of charge itself (a major factor contributing to the degradation of insulation resistance (IR) in electronic components) by minimizing oxygen vacancies. Dielectric materials according to exemplary embodiments of this disclosure satisfy two or more of Equations 1 to 6 above, thereby minimizing the flow of charge moving through grain boundaries and exhibiting a high n-type tendency within the grains, thereby suppressing charge conduction within the grains.
[0029] In one example of this disclosure, the dielectric material according to this disclosure satisfies at least two of the above-described relations 1 to 4. In this disclosure, satisfying at least two relations may mean satisfying two of the above-described relations or satisfying three or more of the above-described relations.
[0030] In the above relationships, Relations 1 through 4 relate to the amount of charge generated within the grain. Rare earth elements tend to act as donors when substituted at the A-site, and as acceptors when substituted at the B-site. Here, the ionic radius can be an important factor in determining which site, A-site or B-site, will be substituted by a rare earth element. Therefore, amphoteric elements such as Dy or Tb selectively substitute at the A-site or B-site, and Ho, Y, etc., with moderate ionic radii, can be used to balance acceptors and donors. Additionally, elements with relatively large ionic radii compared to Dy tend to act as donors, and elements such as Gd, Sm, and Nb, as well as Dy and / or Y, can be used to adjust the balance at the A-site. Furthermore, when the above components are overused, the reliability of electronic components may be relatively degraded. Therefore, when at least two of Relations 1 through 4 are satisfied, similar to the dielectric material in this example, oxygen vacancies within the grain can be minimized to suppress the generation of charge.
[0031] In exemplary embodiments of this disclosure, the dielectric material according to this disclosure may satisfy the above-described relations 5 and 6.
[0032] In the above relationships, Relations 5 and 6 relate to charge transfer at grain boundaries. As mentioned above, the prior art uses the following method: increasing the grain boundary fraction by reducing the size of the grain boundaries, thereby increasing the high resistivity component. However, when Relations 5 and / or 6 are satisfied, a second secondary component with a high work function can be uniformly distributed at the grain interface, thereby suppressing charge release. Furthermore, to balance the dielectric constant and bulk resistivity, the content of a third secondary component for controlling sintering temperature, etc., and / or the content of a first secondary component for suppressing charge transfer within the grains should be considered. Outside of this range, the dielectric constant and reliability may deteriorate.
[0033] In the example, the dielectric material according to this disclosure satisfies at least one of equations 1 to 4, and at least one of equations 5 and 6. In this case, it is possible to achieve bulk resistance within the grain and suppress charge release at grain boundaries.
[0034] In another example, the dielectric material according to this disclosure satisfies at least two of Relations 1 to 4, and also satisfies Relations 5 and 6. That is, the dielectric material according to this disclosure satisfies two or more of Relations 1 to 4, while simultaneously satisfying both Relations 5 and 6. In this example, the reliability within the grain and at grain boundaries can be further improved.
[0035] In exemplary embodiments of this disclosure, the dielectric material according to this disclosure satisfies all of the above-described relations 1 to 6. In this case, it is possible to maximally suppress charge generation and conduction within the grains and high resistance at grain boundaries.
[0036] In another exemplary embodiment of this disclosure, the above relations 1 to 4 may correspond to the following relations 1-1 to 4-1 respectively.
[0037] 0.108≤(M Tb / M Dy ) / M3≤0.800 [Relationship 1-1] 0.118≤(M Gd / M Dy M3 ≤ 0.400 [Relationship 2-1] 0.054≤(M Sm / M Dy ) / M3≤0.118 [Relationship 3-1] 0.054≤(M Nb / M Dy ) / M3≤0.118 [Relationship 4-1] In relations 1-1 to 4-1, M Tb M Dy M Gd M Sm M Nb M3 can have the same meaning as described above. That is, M Tb M Dy M Gd M Sm and M Nb M1 is the sum of the B-site elements relative to 100 moles of the principal component, the number of moles of each component (Tb, Dy, Gd, Sm, and Nb) in the first subcomponent, M2 is the sum of the B-site elements relative to 100 moles of the principal component, and M3 is the total number of moles of the third subcomponent.
[0038] When any one or more of relations 1 to 4 are satisfied, the dielectric material according to this exemplary embodiment may additionally satisfy the corresponding relations 1-1 to 4-1. Relations 1 to 4 correspond to relations 1-1 to 4-1 respectively, which may mean that relations 1 and relations 1-1 correspond to each other, relations 2 and relations 2-1 correspond to each other, relations 3 and relations 3-1 correspond to each other, and relations 4 and relations 4-1 correspond to each other. That is, in this exemplary embodiment, for example, when the dielectric material satisfies relation 1, this may mean that it also satisfies relation 1-1.
[0039] Equations 1-1 to 4-1 relate to the optimal range of the components used to suppress the occurrence of charge in the grain. The first secondary component of the dielectric material according to this disclosure is used to reduce charge conduction in the grain by suppressing the occurrence of oxygen vacancies through a balance of donors and acceptors. Specifically, when the first secondary component substitutes at the A-site and acts as a donor, it is effective in reducing the concentration of oxygen vacancies; however, when used in excess, excessive semiconductorization may occur due to the increased electron concentration, leading to a rapid decrease in insulation resistance. Therefore, Equations 1-1 to 4-1 represent the appropriate range of the content of the first secondary component acting on the Ba-site (i.e., the A-site), and by satisfying Equations 1-1 to 4-1, the bulk resistance in the grain can be increased as much as possible.
[0040] The dielectric material according to exemplary embodiments of this disclosure includes a primary component and secondary components, and the secondary components may include at least one of a first secondary component to a fifth secondary component. In this disclosure, the term "primary component" may refer to a component that occupies a relatively large weight proportion compared to other components, and may refer to a component that constitutes at least 50 wt% of the total weight of the dielectric material. Conversely, "secondary component" may refer to a component that occupies a relatively small weight proportion compared to other components, and may refer to a component that constitutes less than 50 wt% of the total weight of the dielectric material.
[0041] The various components of the dielectric material according to exemplary embodiments of the present disclosure will be described in more detail below.
[0042] a) Principal component Dielectric materials may include those made of (Ba 1-x Ca x (Ti) 1-y (Zr,Sn,Hf) y The principal component is represented by BaTiO3 (0≤x≤1, 0≤y≤0.5). The principal component can be, for example, a compound in which Ca, Zr, Sn, and / or Hf are partially dissolved in BaTiO3. In the above composition formula, x can be in the range greater than or equal to 0 and less than or equal to 1, and y can be in the range greater than or equal to 0 and less than or equal to 0.5, but is not limited thereto. For example, when x is 0 and y is 0 in the above composition formula, the principal component can be BaTiO3.
[0043] b) First sub-component According to exemplary embodiments of the present disclosure, the dielectric material of the present disclosure may include a first secondary component, the first secondary component including at least one element selected from Y, Dy, Ho, Er, Gd, Ce, Nd, Sm, Nb, Tb, Eu, Tm, La, Lu and Yb.
[0044] The content of the first sub-component, relative to the total amount of B-site elements in 100 moles of the main component, can be in the range of greater than or equal to 0.3 moles and less than or equal to 5.7 moles, preferably in the range of greater than or equal to 0.3 moles and less than or equal to 5.4 moles. The content of the first sub-component can be based on the content of at least one element selected from Y, Dy, Ho, Er, Gd, Ce, Nd, Sm, Nb, Tb, Eu, Tm, La, Lu, and Yb, regardless of the type of addition such as oxides or carbonates.
[0045] In an exemplary embodiment of this disclosure, the first sub-component is used to prevent a decrease in the reliability of multilayer ceramic electronic components using dielectric materials. When the first sub-component is outside the aforementioned range, the high-temperature withstand voltage characteristics may deteriorate.
[0046] c) Secondary component According to exemplary embodiments of this disclosure, the dielectric material of this disclosure may include a second sub-component comprising Si and / or Al. The Si element may be introduced during the raw material stage in the form of Si carbonates, oxides, and / or glasses, but may be included in the dielectric layer in the form of oxides and / or glasses after sintering. The Si component is primarily distributed at grain boundaries and has a high work function, thereby increasing the resistance of the grain boundaries. Thus, multilayer ceramic electronic components with excellent reliability can be realized.
[0047] The content of the second sub-component, relative to the total amount of B-site elements in 100 moles of the main component, can be in the range of greater than or equal to 0.5 moles and less than or equal to 6.5 moles, preferably in the range of greater than or equal to 0.5 moles and less than or equal to 5.0 moles. The content of the second sub-component can be based on the content of Si and / or Al elements contained in the second sub-component, regardless of the type of addition such as glass, oxide, or carbonate.
[0048] If the content of the second sub-component is less than 0.5 moles relative to the total amount of B-site elements in 100 moles of the main component, the dielectric constant and high-temperature withstand voltage may decrease, and if the content of the second sub-component exceeds 6.5 moles, the sinterability and density may decrease and a second phase may appear.
[0049] d) Third sub-component According to exemplary embodiments of the present disclosure, the dielectric material of the present disclosure may include a third sub-component comprising Ba and / or Ca.
[0050] The content of the third sub-component can be in the range of greater than or equal to 0.5 moles and less than or equal to 3.0 moles relative to the total amount of B-site elements in 100 moles of the principal component. The content of the third sub-component can be based on the content of at least one of Ba and Ca contained in the third sub-component, regardless of the type of addition such as oxides or carbonates.
[0051] According to this disclosure, the crystal structure of the dielectric material can be controlled by including a third sub-component (the sum of B-site elements relative to 100 moles of the principal component) in an amount greater than or equal to 0.5 moles and less than or equal to 3.0 moles.
[0052] e) Fourth sub-component According to exemplary embodiments of the present disclosure, the dielectric material of the present disclosure may include a fourth sub-component comprising Mg.
[0053] The fourth sub-component can be used as a fixed-valence acceptor element, and its content can be greater than or equal to 0.25 mol and less than or equal to 1.0 mol relative to the total amount of B-site elements in 100 mol of the principal component. The content of the fourth sub-component can be based on the content of Mg element included in the fourth sub-component, regardless of the type of addition such as oxides or carbonates.
[0054] If the content of the fourth sub-component exceeds 1.0 mole relative to the total B-site elements of 100 moles of the main component, problems such as a decrease in dielectric constant and a decrease in high-temperature withstand voltage may occur.
[0055] In the example, the ratio M4 / M3 (e.g., molar ratio) of the content of the fourth sub-component M4 to the content of the third sub-component M3 can satisfy a range greater than or equal to 0.125 and less than or equal to 0.500. By ensuring that the ratio of the fourth sub-component to the third sub-component satisfies the above range, abnormal grain growth of the dielectric material can be suppressed, and uniform grains can be formed.
[0056] f) Fifth sub-component According to exemplary embodiments of the present disclosure, the dielectric material of the present disclosure may include a fifth sub-component, which includes at least one of Mn, V, Cr, Fe, Ni, Co, Cu, and Zn.
[0057] The fifth sub-component can be used as a variable-valence acceptor element, and its content can be greater than or equal to 0.1 mol and less than or equal to 1.0 mol relative to the total amount of B-site elements in 100 mol of the principal component. The content of the fifth sub-component can be based on the content of at least one element from Mn, V, Cr, Fe, Ni, Co, Cu, and Zn contained in the fifth sub-component, regardless of the type of addition such as oxides or carbonates. For example, when 0.1 mol of V₂O₅ (an oxide of V contained in the fifth sub-component) is included, the total amount of V can be 0.2 mol.
[0058] The fifth component is used to improve the resistance to reduction of dielectric materials and to improve the high-temperature withstand voltage characteristics of multilayer ceramic electronic components that use dielectric materials.
[0059] In the example, the dielectric material of this disclosure may include a plurality of grains comprising the main components described above and grain boundaries disposed between two or more grains. Figure 4 This is a schematic diagram illustrating the microstructure of a dielectric material according to exemplary embodiments of the present disclosure. The dielectric material according to the present disclosure can be formed by sintering the main components and secondary components described above, and the dielectric material 111 formed by sintering the main components and secondary components can include grains 11 and grain boundaries 11c.
[0060] The grain 11 may include a core portion 11a and a shell portion 11b, and the shell portion 11b may be configured to surround the core portion 11a. In this case, the average diameter D1 of the core portion 11a may be greater than or equal to 5 nm and less than or equal to 100 nm, and the average diameter D2 of the grain 11 may be greater than or equal to 50 nm and less than or equal to 600 nm. Figure 5 This is a schematic diagram showing grain 11. (Refer to...) Figure 5 The grain 11 may have a core 11a disposed inside the shell 11b. The core 11a may refer to the region in which no byproducts dissolve, and the shell 11b may refer to the region other than the core 11a. The core and shell can be distinguished from each other by analyzing TEM-EDS images of the cut surface.
[0061] The average diameter D1 of the core and the average diameter D2 of the grains can be measured by scanning a cross-section of the body 110 along the length-thickness (LT) direction using a transmission electron microscope (TEM) (10,000x magnification). The core and shell can be distinguished from each other by analyzing the TEM-EDS image. In the TEM-EDS image, the core has a different color than the shell. After selecting 10 grains including the core and shell, the average value obtained by measuring the maximum diameter of each grain can be D2, and the average value obtained by measuring the maximum diameter of the core in each grain can be D1.
[0062] In another exemplary embodiment of this disclosure, the dielectric material according to this disclosure may include: a main component, composed of (Ba 1-x Ca x (Ti) 1-y (Zr,Sn,Hf) y O3 (0≤x≤1, 0≤y≤0.5) represents multiple grains, the surfaces of which are coated with a second sub-component including Si and / or Al, and grain boundaries are provided between two or more grains. Here, the average diameter D1 of the core of the grain can be greater than or equal to 5 nm and less than or equal to 100 nm, and the average diameter D2 of the entire grain can be greater than or equal to 50 nm and less than or equal to 600 nm.
[0063] Figure 6This is a SEM image of barium titanate (BaTiO3) particles with SiO2 coated on their surface. (See reference...) Figure 6 As can be seen, in the steps of preparing the main component and performing heat treatment, Si can be uniformly coated onto the surface of the main component by attaching Si to the surface of the substrate material. When a dielectric material is formed using a main component with Si uniformly coated on its surface, the surface of the grains can be coated with Si, and the effect of improving the resistance of the grain boundaries can be maximized by uniformly distributing Si to the grain boundary regions after sintering.
[0064] This disclosure also relates to a multilayer ceramic electronic component.
[0065] Figure 1 This is a schematic perspective view illustrating a multilayer ceramic electronic assembly according to exemplary embodiments of the present disclosure. Figure 2 It is shown Figure 1 A three-dimensional view of the ceramic body. Figure 3 It is along Figure 1 A cross-sectional view taken from line I-I'. Figure 4 yes Figure 3 A magnified view of region A.
[0066] Reference Figures 1 to 4 The multilayer ceramic electronic assembly 100 according to exemplary embodiments of the present disclosure may include a ceramic body 110, the ceramic body 110 including a dielectric layer 111, a first internal electrode 121, and a second internal electrode 122. The multilayer ceramic electronic assembly 100 according to exemplary embodiments of the present disclosure may include a first external electrode 131 and a second external electrode 132, the first external electrode 131 being located on the outer surface of the ceramic body 110 and connected to the first internal electrode 121, and the second external electrode 132 being located on the outer surface of the ceramic body 110 and connected to the second internal electrode 122. The ceramic body 110 may include a first surface S1 and a second surface S2 opposite to each other in the X direction, a third surface S3 and a fourth surface S4 opposite to each other in the Y direction, and a fifth surface S5 and a sixth surface S6 opposite to each other in the Z direction.
[0067] Here, the dielectric layer may include: made of (Ba 1-x Ca x (Ti) 1-y (Zr,Sn,Hf) y The principal component (or principal component) is represented by O3 (0≤x≤1 and 0≤y≤0.5); the first secondary component (or first auxiliary component) includes at least one element selected from Y, Dy, Ho, Er, Gd, Ce, Nd, Sm, Nb, Tb, Eu, Tm, La, Lu and Yb; the second secondary component includes Si and / or Al; and the third secondary component includes Ba and / or Ca, and can satisfy at least two of the following relations 1 to 6.
[0068] 0.162≤M Tb / M Dy ≤1.20 [Relationship 1] 0.176≤M Gd / M Dy ≤0.60 [Relationship 2] 0.081≤M Sm / M Dy ≤0.176 [Relationship 3] 0.081≤M Nb / M Dy ≤0.176 [Relationship 4] 0.60≤M2 / M1≤1.36 [Equation 5] 0.263≤M3 / M2≤0.455 [Relationship 6] In relations 1 to 4, M Tb M Dy M Gd M Sm and M Nb M1 is the total number of moles of each component (Tb, Dy, Gd, Sm, and Nb) in the first subcomponent relative to 100 moles of the principal component. In Relations 5 and 6, M1 is the total number of moles of the first subcomponent relative to 100 moles of the principal component, M2 is the total number of moles of the second subcomponent relative to 100 moles of the principal component, and M3 is the total number of moles of the third subcomponent relative to 100 moles of the principal component.
[0069] There are no particular restrictions on the specific shape of the ceramic body 110, but as shown in the figure, the ceramic body 110 may have a hexahedral shape or a similar shape. Due to the shrinkage of the ceramic powder particles included in the ceramic body 110 during sintering, the ceramic body 110 may not have a hexahedral shape with perfect straight lines, but may have a substantially hexahedral shape.
[0070] The ceramic body 110 can be formed by alternately stacking ceramic green sheets printed with conductive paste for the first internal electrode 121 and ceramic green sheets printed with conductive paste for the second internal electrode 122 in the thickness direction (Z direction).
[0071] In the ceramic body 110, dielectric layers 111 and internal electrodes 121 and 122 may be stacked alternately in the third direction. The plurality of dielectric layers 111 forming the ceramic body 110 are in a sintered state, and adjacent dielectric layers 111 may become integral, making it difficult to distinguish the boundaries between them without the use of a scanning electron microscope (SEM).
[0072] According to exemplary embodiments of this disclosure, dielectric layer 111 may have a layered structure and may include dielectric layers composed of (Ba 1- x Ca x (Ti) 1-y (Zr,Sn,Hf) y The main component and the aforementioned secondary components are represented by O3 (0≤x≤1 and 0≤y≤0.5). In addition to the aforementioned main and secondary components of the dielectric material, various ceramic additives, organic solvents, plasticizers, binders, dispersants, etc., may be added to the material used to form the dielectric layer 111, according to the purpose of this disclosure.
[0073] The dielectric layer 111 is formed by adding additives as needed to a slurry comprising the main and secondary components described above, coating the resulting slurry onto a carrier film, and drying it to prepare multiple ceramic sheets. The ceramic sheets can be formed by using a doctor blade to fabricate the slurry into sheets with a thickness of several micrometers, but are not limited thereto.
[0074] In another exemplary embodiment of this disclosure, the above relations 1 to 4 may correspond to the following relations 1-1 to 4-1 respectively.
[0075] 0.108≤(M Tb / M Dy ) / M3≤0.800 [Relationship 1-1] 0.118≤(M Gd / M Dy M3 ≤ 0.400 [Relationship 2-1] 0.054≤(M Sm / M Dy ) / M3≤0.118 [Relationship 3-1] 0.054≤(M Nb / M Dy ) / M3≤0.118 [Relationship 4-1] In an exemplary embodiment of this disclosure, the multilayer ceramic electronic component according to this disclosure may further include a fourth sub-component containing Mg, and the ratio (M4 / M3) of the content of the fourth sub-component M4 to the content of the third sub-component M3 may satisfy a range of greater than or equal to 0.125 and less than or equal to 0.500.
[0076] In another exemplary embodiment of this disclosure, the multilayer ceramic electronic component according to this disclosure may include a plurality of grains containing the main components described above and grain boundaries disposed between two or more grains, and the average diameter D1 of the core of the grain may be greater than or equal to 5 nm and less than or equal to 100 nm, and the average diameter D2 of the entire grain may be greater than or equal to 50 nm and less than or equal to 600 nm.
[0077] The dielectric layer may include the aforementioned principal components and the first to fifth sub-components. The contents of the principal components, sub-components, relations, and average diameter are the same as those of the principal components, sub-components, relations, and average diameter described above, and therefore will be omitted.
[0078] The first internal electrode 121 and the second internal electrode 122 may be stacked such that the end surfaces of the first internal electrode 121 and the second internal electrode 122 are respectively exposed at opposite ends of the ceramic body 110. The materials used to form the first internal electrode 121 and the second internal electrode 122 are not particularly limited. For example, the first internal electrode 121 and the second internal electrode 122 may be formed using a conductive paste comprising at least one of silver (Ag), palladium (Pd), gold (Au), platinum (Pt), nickel (Ni), copper (Cu), tin (Sn), tungsten (W), titanium (Ti), and alloys thereof. The conductive paste may be printed using screen printing or gravure printing, but this disclosure is not limited thereto.
[0079] In a multilayer ceramic electronic assembly according to exemplary embodiments of the present disclosure, a first external electrode 131 and a second external electrode 132 may be disposed on the outer surface of a ceramic body. The first external electrode 131 may be connected to a first internal electrode 121, and the second external electrode 132 may be connected to a second internal electrode 122.
[0080] The first external electrode 131 and the second external electrode 132 may include a conductive metal. The conductive metal may be at least one of copper (Cu), nickel (Ni), tin (Sn), palladium (Pd), platinum (Pt), gold (Au), silver (Ag), tungsten (W), titanium (Ti), and lead (Pb), as well as alloys thereof, but is not limited thereto.
[0081] The present disclosure will be described in more detail below with experimental examples, but this is only to aid in understanding the present disclosure, and the scope of the present disclosure is not limited to the experimental examples.
[0082] Experimental Example BaTiO3 powder particles with an average particle size of 30 nm to 100 nm were used as the raw material for the main component. Zirconia balls were used as the mixing / dispersion medium. The raw materials for the main and secondary components corresponding to samples 1 to 54 specified in Table 1 below were mixed with ethanol / toluene and a dispersant, and mechanically ground for 10 hours. After the binder was mixed with the mixture, the mixture was further ground for 10 hours.
[0083] Using the prepared slurry, a green sheet with a thickness of 0.8 μm is produced by spraying through a nozzle on a roll coater. Then, Ni internal electrodes are printed on the green sheet.
[0084] Multilayer green sheets printed with Ni internal electrodes are stacked to form a blank, then a cover sheet is stacked on top of the blank, and ceramic sheets for the edge regions are attached to both sides of the cover sheet and the blank to create a compression rod. The compression rod is cut using a cutter to produce a green blank with 0603 dimensions (length × width × height: 0.6mm × 0.3mm × 0.3mm).
[0085] The completed prototype sheet with a size of 0603 was calcined at about 900°C and sintered at about 1200°C in a reducing atmosphere of 0.1% H2 / 99.9% N2 to 1.0% H2 / 99.0% N2 (H2O / H2 / N2 atmosphere) for a holding time ranging from 10 minutes to 1 hour. It was then heat-treated at 950°C for 3 hours in a N2 atmosphere for re-oxidation.
[0086] The electrical properties of the fabricated prototype wafers were measured, and the density, microstructure uniformity, and presence of a second phase were comprehensively examined. The contents of the following samples were measured by inductively coupled plasma (ICP) analysis, and ICP analysis was performed using an inductively coupled plasma optical emission spectrometer (ICP-OES; Optima 7300DV, PerkinElmer). Furthermore, the presence of each element and the relative ratios between elements were measured using TEM and STEM mapping equipment (such as a Tiatan Cubed G2 60-300 manufactured by FEI).
[0087] [Table 1]
[0088] In Table 1, M RE M is the number of moles of the first component besides Dy. Dy M1 is the total number of moles of the first sub-component, M2 is the total number of moles of the second sub-component, and the coated Si indicates the case where ionized SiO2 oxide is uniformly coated onto the surface of BaTiO3.
[0089] [Table 2]
[0090] Table 2 shows the properties of the prototype sheets corresponding to the samples with the numbers specified in Table 1. In Table 2, M2 is the total number of moles of the second subcomponent, and M3 is the total number of moles of the third subcomponent.
[0091] In Tables 1 and 2, the dielectric constant was measured using an LCR meter at 1 kHz and AC 0.5 V / μm. The dielectric constant of the prototype wafer's dielectric material was calculated from the capacitance, the thickness of the dielectric material, the area of the internal electrodes, and the number of stacks. As a result of the calculations, a dielectric constant less than 1500 was defined as ×, a dielectric constant greater than or equal to 1500 and less than 2000 as △, a dielectric constant greater than or equal to 2000 and less than 3000 as ○, and a dielectric constant greater than or equal to 3000 as ◎.
[0092] Ten samples from the manufactured prototype wafers were selected, and their withstand voltage characteristics were measured by increasing the voltage at DC 10V / μm. A threshold voltage of less than 20V for insulation breakdown was defined as ×, a threshold voltage of 20V or greater but less than 30V as △, a threshold voltage of 30V or greater but less than 40V as ○, and a threshold voltage of 40V or greater as ◎.
[0093] High-temperature reliability was measured under the following conditions: A DC 10V / μm voltage was applied at 105°C using a STEP-IR instrument and maintained for 30 minutes. Subsequently, the voltage was increased, and the IR degradation lifetime was measured. The standard for high-temperature reliability was determined based on the lifetime at which IR degradation occurred. The following conditions were defined: × (time elapsed between 3 and 6 hours for all 10 samples to fail), △ (time elapsed between 6 and 6 hours for all 10 samples to fail), ○ (time elapsed between 10 and 6 hours for all 10 samples to fail), and ◎ (time elapsed between 10 and 10 hours for all 10 samples to fail).
[0094] Regarding the structural characteristics of the samples, the differences in density and average grain size variations observed by SEM in each part of the cross-section and polished surface of the sintered samples were compared. For the density and occurrence frequency of the second phase, a value greater than or equal to 100 for the number of pores (characterized by density in Table 2) and the number of the second phase (characterized by second phase control in Table 2) observed in an image at 50K magnification was defined as ×; a value greater than or equal to 70 and less than 100 for the number of pores and the number of the second phase observed in an image at 50K magnification was defined as △; a value greater than or equal to 40 and less than 70 for the number of pores and the number of the second phase observed in an image at 50K magnification was defined as ○; and a value less than 40 for the number of pores and the number of the second phase observed in an image at 50K magnification was defined as ◎.
[0095] Regarding microstructure uniformity, the case where the standard deviation (STDEV) relative to the overall average grain size is greater than or equal to 150 is defined as ×, the case where the standard deviation (STDEV) relative to the overall average grain size is greater than or equal to 120 and less than 150 is defined as △, the case where the standard deviation (STDEV) relative to the overall average grain size is greater than or equal to 80 and less than 120 is defined as ○, and the case where the standard deviation (STDEV) relative to the overall average grain size is less than 80 is defined as ◎.
[0096] Referring to samples 1 to 8, it can be seen that when M Tb / M Dy When M is less than 0.162, the dielectric constant is excellent, but the structural characteristics, withstand voltage, and high-temperature reliability deteriorate. Furthermore, it can be seen that when M... Tb / M Dy Above 1.20, the structural characteristics are excellent, but electrical characteristics such as withstand voltage and high-temperature reliability deteriorate. Therefore, it can be seen that M... Tb / M Dy The content ratio should meet the range of greater than or equal to 0.162 and less than or equal to 1.20.
[0097] Referring to samples 9 to 15, it can be seen that when M Gd / M Dy When M is less than 0.176, the structural characteristics and dielectric constant are excellent, but the withstand voltage and high-temperature reliability deteriorate. Furthermore, it can be seen that when M... Gd / M Dy When the value exceeds 0.60, electrical characteristics such as withstand voltage and high-temperature reliability deteriorate. Therefore, it can be seen that M... Gd / M Dy The content ratio should meet the range of greater than or equal to 0.176 and less than or equal to 0.60.
[0098] Referring to samples 16 to 22, it can be seen that when M Sm / M Dy When the dielectric constant exceeds 0.176, an excellent dielectric constant is obtained, but electrical characteristics such as withstand voltage and high-temperature reliability deteriorate. Therefore, it can be seen that M... Sm / M Dy The content ratio should be within the range of greater than or equal to 0.081 and less than or equal to 0.176.
[0099] Referring to samples 23 to 29, it can be seen that when M Nb / M Dy When the dielectric constant exceeds 0.176, an excellent dielectric constant is obtained, but electrical characteristics such as withstand voltage and high-temperature reliability deteriorate. Therefore, it can be seen that M... Nb / M DyThe content ratio should be within the range of greater than or equal to 0.081 and less than or equal to 0.176.
[0100] Referring to samples 30 to 49, it can be seen that even when the same amount of the first sub-component is used, if the amount of the second sub-component is added at a ratio outside the appropriate range, the dielectric constant and density decrease. Furthermore, it can be seen that even when the same amount of Si is used, the dielectric constant decreases when its ratio to the third sub-component is outside the predetermined range. Therefore, it can be seen that even when the first sub-component corresponding to the rare earth element has the same amount, the ratio of the second and third sub-components has a significant impact.
[0101] Samples 50 to 54 show the results using a main component coated with Si on its surface. Referring to samples 50 to 54, it can be seen that when Si is uniformly distributed on the surface of the main component, excellent electrical properties are obtained even when the content of the first secondary component varies. That is, it can be seen that when Si is controlled to be uniformly distributed on the surface of the main component, the interfacial resistance of the grain boundaries can be improved more effectively.
[0102] As described above, one of the effects of this disclosure provides dielectric materials and multilayer ceramic electronic components with high dielectric constant and excellent withstand voltage characteristics.
[0103] According to one of the effects of this disclosure, dielectric materials and multilayer ceramic electronic components with excellent high-temperature withstand voltage are provided.
[0104] One of the various effects of this disclosure is to provide dielectric materials and multilayer ceramic electronic components that can control the dielectric density and microstructure uniformity of the second phase.
[0105] While exemplary embodiments have been shown and described above, it will be readily understood by those skilled in the art that modifications and variations may be made without departing from the scope of this disclosure as defined by the appended claims.
Claims
1. A dielectric material, comprising: Principal component, composed of (Ba 1-x Ca x (Ti) 1-y (Zr,Sn,Hf) y O3 represents the condition where 0 ≤ x ≤ 1 and 0 ≤ y ≤ 0.5; The first component includes at least one element selected from Y, Dy, Ho, Er, Gd, Ce, Nd, Sm, Nb, Tb, Eu, Tm, La, Lu, and Yb; The second component includes Si and / or Al; and The third component includes Ba and / or Ca. Among them, at least two of the following relations 1 to 4 are satisfied: 0.162≤M Tb / M Dy ≤1.20 [Relationship 1] 0.176≤M Gd / M Dy ≤0.60 [Relationship 2] 0.081≤M Sm / M Dy ≤0.176 [Relationship 3] 0.081≤M Nb / M Dy ≤0.176 [Relation 4], Among them, in relation 1 to relation 4, M Tb M Dy M Gd M Sm and M Nb These are the sum of the B-site elements relative to 100 moles of the principal component, and the number of moles of Tb, Dy, Gd, Sm, and Nb in the first sub-component.
2. The dielectric material according to claim 1, wherein, The second sub-component is Si.
3. The dielectric material according to claim 1, wherein, Satisfying relations 5 and 6, 0.60≤M2 / M1≤1.36 [Equation 5] 0.263≤M3 / M2≤0.455 [Equation 6] In Relations 5 and 6, M1 is the total number of moles of the first subcomponent relative to 100 moles of the principal component at the B site, M2 is the total number of moles of the second subcomponent relative to 100 moles of the principal component at the B site, and M3 is the total number of moles of the third subcomponent relative to 100 moles of the principal component at the B site.
4. The dielectric material according to claim 1, wherein, Satisfies at least one of relations 5 and relations 6. 0.60≤M2 / M1≤1.36 [Equation 5] 0.263≤M3 / M2≤0.455 [Equation 6] In Relations 5 and 6, M1 is the total number of moles of the first subcomponent relative to 100 moles of the principal component at the B site, M2 is the total number of moles of the second subcomponent relative to 100 moles of the principal component at the B site, and M3 is the total number of moles of the third subcomponent relative to 100 moles of the principal component at the B site.
5. The dielectric material according to claim 1, wherein, The third sub-component is Ba.
6. The dielectric material according to claim 1, wherein, 0.60≤M2 / M1≤1.36 [Equation 5] 0.263≤M3 / M2≤0.455 [Relationship 6] In Relations 5 and 6, M1 is the total number of moles of the first subcomponent relative to the sum of the B-position elements of 100 moles of the principal component; M2 is the total number of moles of the second subcomponent relative to the sum of the B-position elements of 100 moles of the principal component; and M3 is the total number of moles of the third subcomponent relative to the sum of the B-position elements of 100 moles of the principal component. It satisfies relations 1 to 6.
7. The dielectric material according to any one of claims 1 to 6, wherein, Relations 1, 2, 3, and 4 correspond to relations 1-1, 2-1, 3-1, and 4-1, respectively, and When at least two of the following conditions are met: relation 1, relation 2, relation 3, and relation 4, the corresponding relations in relation 1-1, relation 2-1, relation 3-1, and relation 4-1 are also met: 0.108≤(M Tb / M Dy ) / M3≤0.800 [Relationship 1-1] 0.118≤(M Gd / M Dy M3 ≤ 0.400 [Relationship 2-1] 0.054≤(M Sm / M Dy ) / M3≤0.118 [Relationship 3-1] 0.054≤(M Nb / M Dy ) / M3≤0.118 [Relation 4-1], M3 is the sum of the B-site elements of the principal component relative to 100 moles, and the total number of moles of the third sub-component.
8. The dielectric material according to claim 1, wherein, The content of the third sub-component is within the range of greater than or equal to 0.5 moles and less than or equal to 3.0 moles relative to the total amount of B-site elements in 100 moles of the principal component.
9. The dielectric material according to claim 1, wherein the dielectric material further comprises: The fourth component includes Mg. Wherein, relative to the sum of the B-site elements of 100 moles of the principal component, the content M4 of the fourth sub-component satisfies the range of greater than or equal to 0.25 moles and less than or equal to 1.0 moles.
10. The dielectric material according to claim 9, wherein, The molar ratio M4 / M3 of the fourth sub-component to the content M3 of the third sub-component satisfies a range greater than or equal to 0.125 and less than or equal to 0.
500. M3 is the sum of the B-site elements of the principal component relative to 100 moles, and the total number of moles of the third sub-component.
11. The dielectric material according to claim 1, wherein, Relative to the sum of the B-site elements of 100 moles of the principal component, the content of the first secondary component satisfies a range of greater than or equal to 0.3 moles and less than or equal to 5.7 moles, and The content of the second sub-component is in the range of greater than or equal to 0.5 mol and less than or equal to 6.5 mol relative to the sum of the B-site elements of 100 mol of the principal component.
12. The dielectric material according to claim 1, wherein the dielectric material further comprises: The fifth component includes at least one of Mn, V, Cr, Fe, Ni, Co, Cu, and Zn, and The content of the fifth sub-component is in the range of greater than or equal to 0.1 mol and less than or equal to 1.0 mol relative to the sum of the B-site elements of 100 mol of the principal component.
13. The dielectric material according to claim 1, further comprising grains containing the main component and grain boundaries disposed between two or more grains, wherein, The average diameter D1 of the core of the grain is greater than or equal to 5 nm and less than or equal to 100 nm, and the average diameter D2 of the grain is greater than or equal to 50 nm and less than or equal to 600 nm.
14. The dielectric material according to claim 13, wherein the surface of the grain is coated with the second sub-component.
15. A multilayer ceramic electronic component, comprising: The ceramic body includes a dielectric layer and a first internal electrode and a second internal electrode; as well as A first external electrode and a second external electrode are disposed on the outer surface of the ceramic body and are respectively connected to the first internal electrode and the second internal electrode. The dielectric layer comprises: a main component, consisting of (Ba... 1-x Ca x (Ti) 1-y (Zr,Sn,Hf) y O3 represents a structure where 0 ≤ x ≤ 1 and 0 ≤ y ≤ 0.5; the first subcomponent includes at least one element selected from Y, Dy, Ho, Er, Gd, Ce, Nd, Sm, Nb, Tb, Eu, Tm, La, Lu, and Yb; the second subcomponent includes Si and / or Al; and the third subcomponent includes Ba and / or Ca, and satisfies at least two of the following relations 1 to 4: 0.162≤M Tb / M Dy ≤1.20 [Relationship 1] 0.176≤M Gd / M Dy ≤0.60 [Relationship 2] 0.081≤M Sm / M Dy ≤0.176 [Relationship 3] 0.081≤M Nb / M Dy ≤0.176 [Relation 4], Among them, in relation 1 to relation 4, M Tb M Dy M Gd M Sm and M Nb These are the sum of the B-site elements relative to 100 moles of the principal component, and the number of moles of Tb, Dy, Gd, Sm, and Nb in the first sub-component.
16. The multilayer ceramic electronic component according to claim 15, wherein, Relations 1, 2, 3, and 4 correspond to relations 1-1, 2-1, 3-1, and 4-1, respectively, and When the dielectric layer satisfies at least two of the following relationships: Equation 1, Equation 2, Equation 3, and Equation 4, it also satisfies the corresponding relationships in Equations 1-1, Equation 2-1, Equation 3-1, and Equation 4-1: 0.108≤(M Tb / M Dy ) / M3≤0.800 [Relationship 1-1] 0.118≤(M Gd / M Dy M3 ≤ 0.400 [Relationship 2-1] 0.054≤(M Sm / M Dy ) / M3≤0.118 [Relationship 3-1] 0.054≤(M Nb / M Dy ) / M3≤0.118 [Relation 4-1], M3 is the sum of the B-site elements of the principal component relative to 100 moles, and the total number of moles of the third sub-component.
17. The multilayer ceramic electronic component according to claim 15, further comprising: The fourth component includes Mg, and The molar ratio M4 / M3 of the content of the fourth sub-component M4 to the content of the third sub-component M3 satisfies a range greater than or equal to 0.125 and less than or equal to 0.
500. M3 is the sum of the B-site elements relative to 100 moles of the principal component, the total number of moles of the third sub-component, M4 is the sum of the B-site elements relative to 100 moles of the principal component, and the content of the fourth sub-component.
18. The multilayer ceramic electronic component according to claim 15, wherein, The dielectric layer includes: Multiple grains, including the principal component, with grain boundaries disposed between two or more grains. Wherein, the average diameter D1 of the core of the grain is greater than or equal to 5 nm and less than or equal to 100 nm, and the average diameter D2 of the grain is greater than or equal to 50 nm and less than or equal to 600 nm.
19. The multilayer ceramic electronic component according to claim 18, wherein, The second sub-component is coated on the surface of the plurality of grains.
20. The multilayer ceramic electronic component according to claim 15, wherein, The second sub-component is Si, and the third sub-component is Ba.
21. The multilayer ceramic electronic component according to claim 15, wherein, The following condition is satisfied: 0.60 ≤ M2 / M1 ≤ 1.36, where M1 is the total number of moles of the first subcomponent relative to 100 moles of the principal component at the B site, and M2 is the total number of moles of the second subcomponent relative to 100 moles of the principal component at the B site.
22. The multilayer ceramic electronic component according to claim 15, wherein, The following condition is satisfied: 0.60 ≤ M2 / M1 ≤ 1.36, where M1 is the total number of moles of the first subcomponent relative to the sum of the B-site elements of 100 moles of the principal component, and M2 is the number of moles of Si relative to the sum of the B-site elements of 100 moles of the principal component.
23. The multilayer ceramic electronic component according to claim 15, wherein, The following condition is satisfied: 0.263 ≤ M3 / M2 ≤ 0.455, where M2 is the sum of the B-site elements of 100 moles of the principal component, the total number of moles of the second subcomponent, and M3 is the sum of the B-site elements of 100 moles of the principal component, the total number of moles of the third subcomponent.
24. The multilayer ceramic electronic component according to claim 15, wherein, The condition 0.263 ≤ M3 / M2 ≤ 0.455 is satisfied, where M2 is the total number of moles of Si relative to the sum of B-site elements of 100 moles of the principal component, and M3 is the total number of moles of the third sub-component relative to the sum of B-site elements of 100 moles of the principal component.
Citation Information
Patent Citations
Dielectric ceramic composition and multilayer ceramic capacitor comprising the same
US20200251242A1
